From day to day : one man's diary of survival in Nazi concentration camps - Nansen, Odd, 1901-1973 (Vanderbilt University Press, 2016)
""From Day to Day, a World War II concentration camp diary, one of the very few to survive, records the author's struggle, not only to survive, but to maintain his humanity, amidst the casual brutality and random terror that was the fate of a camp prisoner"--Provided by publisher"--